Triple Network Model Dynamically Revisited: Lower Salience Network State Switching in Pre-psychosis - Bolton, Thomas A. W.; Wotruba, Diana; Buechler, Roman; Theodoridou, Anastasia; Michels, Lars; Kollias, Spyros; Rössler, Wulf; Heekeren, Karsten; Van De Ville, Dimitri (Frontiers in Physiology, 2020)
Emerging evidence has attributed altered network coordination between the default mode, central executive and salience networks (DMN/CEN/SAL) to disturbances seen in schizophrenia, but little is known for at-risk psychosis stages. Moreover, pinpointing impairments in specific network-to-network interactions, although essential to resolve possibly distinct harbingers of conversion to clinically diagnosed schizophrenia, remains particularly challenging. We addressed this by a dynamic approach to functional connectivity, where right anterior insula (rAI) brain interactions were examined through co-activation pattern (CAP) analysis. We utilized resting-state fMRI in 19 subjects suffering from subthreshold delusions and hallucinations (UHR), 28 at-risk for psychosis with basic symptoms describing only self-experienced subclinical disturbances (BS), and 29 healthy controls (CTR) matched for age, gender, handedness and intelligence. We extracted the most recurring CAPs, compared their relative occurrence and average dwell time to probe their temporal expression, and quantified occurrence balance to assess the putative loss of competing relationships. Our findings substantiate the pivotal role of the rAI in governing CEN-to-DMN transitions, which appear dysfunctional prior to the onset of psychosis, especially when first attenuated psychotic symptoms occur. In UHR subjects, the rAI is longer active in concert with the DMN and there is a loss of competition between a SAL/DMN state, and a state with rAI/CEN activation paralleled by DMN deactivation. These features suggest that abnormal network switching disrupts one’s capacity to distinguish between the internal world and external environment, which is accompanied by inflexibility and an excessive awareness to internal processes reflected by prolonged expression of the rAI-DMN co-activation pattern.